Prevalence of aberrant dental morphological details in 6-10 year old school children in an Indian population - M Kirthiga; M Manju; R Praveen; W Umesh (Wolters Kluwer Medknow Publications, 2015)
Background: Variations in the structure of teeth have always been a great curiosity to the dentist from the scientific and practical point of view. Aim: To evaluate the prevalence of a few aberrant morphological features namely, cusp of Carabelli in primary maxillary second molar and in permanent first molar, five cusp in primary maxillary second molar and permanent first molar, shoveling and double shoveling with respect to permanent maxillary central incisors, four cusped primary mandibular second molar and permanent first molar, six cusped primary mandibular second molar and permanent first molar and seven cusped primary mandibular second molar and permanent first molar in 6-10 year old children belonging to the East Bengaluru, a City in India. Design: A cross-sectional survey was conducted among 2111 children by two stage sampling method. Type III examination was performed. The findings were subjected to Chi-square test. Results: 83.8% of the studied population had one or more of the variations checked for, as mentioned above. The variation most commonly seen was double shoveling (66.6%) followed by shoveling (65.7%). No significant results were observed in any trait with respect to gender.Conclusion: This study is the first of its kind, providing a baseline data of the prevalence of morphological details in the pediatric Indian population.